Science Policy Conference on Gender-Responsive Climate-Smart Agriculture for Eastern, Central and Southern Africa - Osumba, Joab; Ndetun, Veronica; Rapando, Nancy; Lokorito, Cromwel; Kimani, Lydia; Manei, Priscilla Karobia; Kuria, Peter; Owuonda, Salome; Gikunda, Faith; Mate, Harold; Barungi, Julian; Recha, John W.M. (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
The content of this report is a mixed bag of experiences and lessons, from plain field experience and case stories to document reviews and rigorous scientific results, all generating credible evidence to inform policy. In each breakout room, participants had a very vibrant engagement with the presenters, eliciting very valuable lessons.